The non-pharmacological treatment of primary dysmenorrhea - efficiency and safety - Brygida Zapała; Aldona Ząber; Ewa Gacoń; Julita Zembala; Nikola Siekierko; Jakub Kucharski; Maja Żołnierek; Wiktoria Kotusiewicz; Mateusz Mirosław Lewandowski (Kazimierz Wielki University, 2023)
Primary dysmenorrhea  is the most common, though often underdiagnosed, gynecological disorder of women of reproductive age. The disease presents with painful abdominal cramps associated with menstrual bleeding in the absence of pelvic abnormalities. Symptoms are caused primarily by increased levels of prostaglandins produced by the endometrium, which provides hypercontraction of the uterine muscles, ischemia, and pain.  Dysmenorrhea is usually treated pharmacologically with non-steroidal anti-inflammatory drugs or hormonal contraception. In particularly severe cases, surgical treatment is also possible. Nonetheless, an increasing amount of studies on non-pharmacological treatments have been published recently. Methods like Transcutaneous Electrical Nerve Stimulation (TENS), acupuncture, continuous topical heat, or exercise and yoga seem to be effective in reducing the symptoms of primary dysmenorrhea. All have an anti-inflammatory effect by lowering prostaglandin levels, but they also contribute to reducing symptoms through other mechanisms. TENS elevates the pain threshold and, together with acupuncture, causes the release of endogenous opioids. Heat, yoga, and acupuncture also lead to increased blood flow in the uterus, reducing hypoxia. Their additional advantage is the low cost and ease of self-use, except for acupuncture, depending on the patient's needs. Side effects of non-pharmacological treatments are usually mild and rarely reported.